Analysis of Consumptive Behavior of Students Who Follow the Outfit of the Day (OOTD) Trend on the Tiktok Application - Fitri, Azizah Ayu; Suyanto, Edy; Lestari, Soetji (Program Studi Pendidikan IPS, 2024)
This consumptive lifestyle is fully controlled by marketing techniques that control the entire awareness of consumer society. Especially when it comes to differentiation. Thus, consumer society will see their self-identity or freedom as freedom to project their desires on industrial goods (Baudrillard). It is felt that video content posted on TikTok can convey information in a short and interesting manner, this is used by entrepreneurs for advertising media which then gave rise to the phenomenon of the OOTD (Outfit of The Day) tren. The lifestyle created by social media has created a consumptive lifestyle, namely hedonism and westernization among young Indonesians. In this study using a qualitative research method is to describe factually regarding the facts of the field and the characteristics that exist in the object of research qualitatively. The results of this study found that the outfit of the day tren in the tiktok application can lead to consumptive behavior among students. the tendency to behave consumptively causes students to buy without paying attention to the use of these goods because students now have a considerable interest in following the trens circulating in the market.